Persepsi Peserta Program Kampus Mengajar Dalam Mempraktekkan Kemampuan Public Speaking - Sylla Fazira Silaban; Nurhasanah Nasution (KESKAP: Jurnal Kesejahteraan Sosial, Komunikasi dan Administrasi Publik, 2023)
This research is discusses the perceptions or experiences of campus participants teaching during their assignment in schools that are classified as 3T, namely frontier, remote, and underdeveloped to help equalize education in Indonesia by way of students being able to directly develop themselves through dedication and have activities outside the scope of the world of lectures. so that they can find solutions and help improve the world of education in Indonesia, especially discussing how the participants practice public speaking skills during the teaching and learning process. Where this study aims to find out how effective public speaking is to attract and shape the character of elementary school age children, as well as what interactions students build outside the campus environment both using verbal and non-verbal communication and what methods and innovations are used by campus participants to teach in arouse the interest of early childhood to develop themselves both intellectual abilities and physical abilities